Semaphorin Signaling in the Development and Function of the Gonadotropin Hormone-Releasing Hormone System - Messina, Andrea; Giacobini, Paolo (Frontiers in Endocrinology, 2013)
The semaphorin proteins are among the best-studied families of guidance cues, contributing to morphogenesis and homeostasis in a wide range of tissue types. The major semaphorin receptors are plexins and neuropilins, however other receptors and co-receptors are capable to mediate signaling by semaphorins. These guidance proteins were originally identified as growth cone “collapsing factors” or as inhibitory signals, crucial for nervous system development. Since those seminal discoveries, the list of functions of semaphorins has rapidly grown. Over the past few years, a growing body of data indicates that semaphorins are involved in the regulation of the immune and vascular systems, in tumor growth/cancer cell metastasis and in neural circuit formation. Recently there has been increasing emphasis on research to determine the potential influence of semaphorins on the development and homeostasis of hormone systems and how circulating reproductive hormones regulate their expression and functions. Here, we focus on the emerging role of semaphorins in the development, differentiation and plasticity of unique neurons that secrete gonadotropin-releasing hormone (GnRH), which are essential for the acquisition and maintenance of reproductive competence in all vertebrates. Genetic evidence is also provided showing that insufficient semaphorin signaling contributes to some forms of reproductive disorders in humans, characterized by the reduction or failure of sexual competence. Finally, we will review some studies with the goal of highlighting how the expression of semaphorins and their receptors might be regulated by gonadal hormones in physiological and pathological conditions.